HUBUNGAN KORPORA AMILASEA DENGAN PROSTATITIS, BENIGN PROSTAT HIPERPLASIA, DAN KARSINOMA PROSTAT PADA TURP DI RSUD ARIFIN ACHMAD PROPINSI RIAU PERIODE 2008-2013 - Alcan, Firdath Rubenzani; ", Zuhirman; Malik, Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Corpora amylacea is a substance of protein secret produced by gland epithelial cell when the gland shape changed. Prostatitis is an inflammation of the prostate. Benign prostate hyperplasia is a benign enlargement of the prostate varied from gland hyperplasia or fibromuscular hyperplasia. Carcinoma of the prostate is an abnormal growth of the prostate cells. This study uses the medical record of pathological examination in the Anatomic Pathology Department Arifin Achmad Hospital of Riau Province. Based on correlation of prostatitis, benign prostate hyperplasia and carcinoma of the prostate with corpora amylacea, benign prostate hyperplasia has the strongest correlation (0.214) then prostatitis (-0.63) and carcinoma of the prostate (-0.233). The conclusion is corpora amylacea has the strongest relation with benign prostate hyperplasia, then followed by prostatitis and carcinoma of the prostateKeywords : Corpora amylacea, prostatitis, BPH and Ca prostate.